Range expansion of the Asian native giant resin bee Megachile sculpturalis (Hymenoptera, Apoidea, Megachilidae) in France. Issue 3 (2nd January 2018) - Le Féon, Violette; Aubert, Matthieu; Genoud, David; Andrieu‐Ponel, Valérie; Westrich, Paul; Geslin, Benoît
Abstract: In 2008, a new species for the French bee fauna was recorded in Allauch near Marseille: the giant resin bee, Megachile sculpturalis (Smith, 1853). This was the first European record of this species that is native to East Asia. To our knowledge, it is the first introduced bee species in Europe. Here, we provide an overview of the current distribution of M. sculpturalis in France and we describe the history of its range expansion. Besides our own observations, information was compiled from literature and Internet websites, and by contacting naturalist networks. We collected a total of 117 records ( locality  ×  year combinations) for the 2008–2016 period. The geographical range of M. sculpturalis has extended remarkably, now occupying a third of continental France, with the most northern and western records located 335 and 520 km from Allauch, respectively. Information on its phenology, feeding, and nesting behavior is also provided. We report several events of nest occupation or eviction of Osmia sp. and Xylocopa sp. individuals by M. sculpturalis . Our results show that M. sculpturalis is now well established in France. Given its capacity to adapt and rapidly expand its range, we recommend amplifying the monitoring of this species to better anticipate the changes in its geographical range and its potential impacts on native bees. Abstract : In 2008, a new species for the French bee fauna was recorded in Allauch near Marseille: the giant resin bee, Megachile sculpturalis (Smith, 1853). This was the first European record of this species native from East Asia. Here, we provide an overview of the current distribution of M. sculpturalis in France and we describe its expansion history.